Report on "Problem Solving in Mathematics Education": ProMath 6 Conference, 8–11 September, 2005, Debrecen, Hungary (Teaching Mathematics and Computer Science, 2005)
The sixth ProMath Conference was organized at the University of Debrecen (Hungary) in the year 2005. There were 12 presentations. After a short historical introduction we present the 12 abstracts written by the authors.